“It takes two”: Women’s empowerment in agricultural value chains - Ragasa, Catherine; Malapit, Hazel J.; Rubin, Deborah; Myers, Emily; Pereira, Audrey; Martinez, Elena M.; Heckert, Jessica; Seymour, Greg; Mzungu, Diston; Kalagho, Kenan; Kazembe, Cynthia; Thunde, Jack; et al. (International Food Policy Research Institute, 2021)
This brief summarizes the recent assessment of the implementation of the Agricultural Technical and Vocational Education Training for Women Program (ATVET4Women) that aims to support women and their families with vocational training and market linkages in priority agricultural value chains (VCs). The ATVET4Women program has two main components: formal training and nonformal training. Formal training consists of a 2- or 3-year vocational and technical course at an agricultural training center (ATC) where students gain skills (and a diploma) for employment or entrepreneurship in the agricultural sector. Nonformal training provides farmers with 1 to 3 weeks of training on good production and business management practices.